(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The landscape of global trade is continuously evolving, influenced by a myriad of factors including technological advancements, policy changes, and economic shifts. Understanding these dynamics is crucial for businesses, policymakers, and economists alike. This article delves into the current trends in international commerce, highlighting key drivers and their implications for global markets.